With my little eye ebook A novel. - Jackson, Joshilyn (2023)
From the New York Times bestselling author of Never Have I Ever comes the hair-raising story of a mother who moves herself and her daughter across the country to escape a dangerous stalker— but she can't keep herself and her daughter safe from a monster she can't identify HIS GAME. HIS RULES. HER LIFE. It started with the letters... For actress Meribel Mills, disturbing fan mail is part of the price of fame. So when she starts getting creepy letters written in fruit-scented marker she's mostly unfazed. But there's something different about Marker Man... He's been in her home... Meribel's sheets smell of unfamiliar cologne, and objects are changing places inside her house. While the police insist that stalkers hardly ever escalate to violence, Meribel has played the dead girl one too many times on TV to risk becoming her in real life. She and her daughter move from Los Angeles to Atlanta for a fresh start—but no distance is great enough. He's watching her... Years of being in front of a camera have given Meribel a superpower—she can feel eyes on her, and someone definitely has her in their sights. Could Marker Man have followed her all the way across the country? Suddenly, every man in her life is a suspect and Meribel finds herself in the fight of her life, desperate to protect those she loves as danger closes in from all sides. If he can't have her, no one can. Look for these other pulse-pounding thrillers by New York Times bestselling author Joshilyn Jackson: Mother May I Never Have I Ever